2015
DOI: 10.1242/jeb.114868
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical challenges to freshwater residency in sharks and rays

Abstract: Major transitions between marine and freshwater habitats are relatively infrequent, primarily as a result of major physiological and ecological challenges. Few species of cartilaginous fish have evolved to occupy freshwater habitats. Current thought suggests that the metabolic physiology of sharks has remained a barrier to the diversification of this taxon in freshwater ecosystems. Here, we demonstrate that the physical properties of water provide an additional constraint for this species-rich group to occupy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Adult movement away from inshore regions may be the result of changes in diet or resource needs, or could be a mechanism to reduce competition or avoid predation on kin. Recent research by Gleiss et al (2015) has also suggested liver density may play a role in use of freshwater regions by elasmobranch species. It is thus possible that previously unconsidered biological drivers are also at work.…”
Section: Discussionmentioning
confidence: 99%
“…Adult movement away from inshore regions may be the result of changes in diet or resource needs, or could be a mechanism to reduce competition or avoid predation on kin. Recent research by Gleiss et al (2015) has also suggested liver density may play a role in use of freshwater regions by elasmobranch species. It is thus possible that previously unconsidered biological drivers are also at work.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the data collected here, ascent TBAA is much higher than descent TBAA, and ascent TBC is shorter duration than descent TBC, showing that sharks beat their tail harder and faster while ascending than while descending. This is likely due to their lack of a swim bladder and negative buoyancy (Baldridge, 1970;Gleiss et al, 2015), which makes ascending more work than descending (Gleiss et al, 2011;Nakamura et al, 2011;Weihs, 1977). Thus individuals chose to exert additional energy performing low-cost behaviors (such as descents) during recovery, possibly to increase water flow over the gills, but not in high-cost behaviors (such as ascents; Gleiss et al, 2011).…”
Section: Evaluation Of Swimming Metricsmentioning
confidence: 99%
“…While the majority of tag validation studies to date have cited tag mass as a key determinant of tag suitability, studies ought to move away from this paradigm and provide systematic assessments of hydrodynamic drag and alterations to buoyancy, which are arguably more relevant to aquatic animals. Furthermore, buoyancy control represents a substantial energetic investment for elasmobranchs, including juveniles that are typically less buoyant than adults (Gleiss et al, 2015;Iosilevskii & Papastamatiou, 2016). Therefore, small juvenile N. brevirostris experienced alterations in activity levels, swimming kinematics and swimming performance by carrying external telemetry packages.…”
Section: Discussionmentioning
confidence: 99%